1988
DOI: 10.1042/bj2530851
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rabbit acute phase protein biosynthesis by monokines

Abstract: We defined the acute phase behaviour of a number of rabbit plasma proteins in studies (in vivo) and studied the effects of monokine preparations on their synthesis by rabbit primary hepatocyte cultures. Following turpentine injection, increased serum levels of C-reactive protein, serum amyloid A protein, haptoglobin, ceruloplasmin, and decreased concentrations of albumin were observed. In contrast to what is observed in man, concentrations of alpha 2-macroglobulin and transferrin were increased. Co-culture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…12 Of the inflammatory markers, CRP is synthesized by the liver in response to interleukin-1, interleukin-6 and other cytokines. 17 Increased CRP levels show both the activity of this chronic disease and make up an independent risk factor for atherosclerosis 8,18 and arrhythmias. 19 Elevated ESR and leucocytes are expected findings in this chronic inflammatory process and were shown in previous studies to be associated with cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…12 Of the inflammatory markers, CRP is synthesized by the liver in response to interleukin-1, interleukin-6 and other cytokines. 17 Increased CRP levels show both the activity of this chronic disease and make up an independent risk factor for atherosclerosis 8,18 and arrhythmias. 19 Elevated ESR and leucocytes are expected findings in this chronic inflammatory process and were shown in previous studies to be associated with cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a is thought to be one of the host-derived factors that leads to the mobilization of energy stores during the acutephase response (26) to tissue injury, infection, or chronic disease states, including cancer (27,28). TNF-a is also important in the immune response and hematopoiesis, as it stimulates the synthesis of other cytokines, such as interleukin 1 (29), interleukin 6 (30), and granulocyte-macrophage colony-stimulating factor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown important variation in the APP response among species. APP were first characterised in humans [20], rodents [19,22] and later in other animal species, such as pigs [13,21]. Clinical use of APP determination has been proposed in veterinary medicine to determine the health status of farm animals in various production processes [14,28,39].…”
Section: Introductionmentioning
confidence: 99%